The Effect of Online Education on Children’s Socialization Processes During the Pandemic Period: A Communication- Based Research on First Grade Primary School Students - YAZGAN, AYŞE MÜGE; ÖZGEN, EBRU (My University, 2024)
Isolated life emerged at a time when society was not ready during the 2020 pandemic (Covid-19) period. During this period, the structure of society, which has undergone significant social changes, has been transformed. It has been vital to adapt rapidly to the social isolation and distance from outside life within this new social structure. Digital technology is also a factor that changed the lives of students at school. The scope of this research includes 3rd-grade students in primary schools in three major cities of Türkiye: İstanbul, Ankara, and İzmir. This research aims to gather information about the social changes and social anxiety of the students during social isolation by analyzing the responses to scale questions used as a data collection tool, under the observation of parents and classroom teachers. The research design incorporates both quantitative and qualitative methodologies. The data collection tools used in this study are the SocialEmotional and Character Development Scale in the survey research, the Social Anxiety Scale for Children, and a personal information form prepared by the researchers. Results are augmented with semi-structured interviews. Data analysis is conducted using the SPSS 22.0 statistical software package. The results obtained indicate that students experience social anxiety as a result of isolation. It is observed that during the Covid-19 pandemic period, social isolation affected 1st-grade students in the 2020-2021 academic year. The findings suggest that as the level of social anxiety and social change increase, there is a decrease in social, emotional, and moral development. Keywords: Covid-19, Pandemic, Social Isolation, Anxiety, Social Change, Digital Technology

İzole yaşam, 2020 pandemi (Covid-19) döneminde, toplumun hazır olmadığı bir anda ortaya çıkmıştır. Bu süreçte, toplumsal değişim gösteren toplumun yapısı değişmiştir. Bu yeni toplumsal yapı içerisinde yer alan sosyal izolasyona ve dışardaki yaşamdan uzaklaşmaya hızlı uyum gösterilmesi zorunlu olmuştur. Dijital teknoloji aynı zamanda okuldaki öğrencilerin hayatlarını da değiştirmiştir. Bu araştırmanın evrenini Türkiye’nin üç büyük ili olan İstanbul, Ankara ve İzmir’de bulunan ilkokul 3. sınıf öğrencileri oluşturmaktadır. Bu araştırma, velilerin ve sınıf öğretmenlerinin gözlemi altında veri toplama aracı olarak kullanılan ölçek sorularına verilen cevaplar sonucunda öğrencilerin sosyal izolasyon sırasındaki sosyal değişimleri ve sosyal kaygıları hakkında bilgi toplamayı amaçlamaktadır. Araştırma tasarımı nicel ve nitel araştırmaya dayanmaktadır. Bu çalışmada kullanılan veri toplama araçları, anket araştırmasında yer alan sosyal-duygusal ve karakter gelişimi ölçeği, çocuklara yönelik sosyal kaygı ölçeği ve araştırmacılar tarafından hazırlanan kişisel bilgi formudur. Sonuçlar yarı-derinlemesine görüşmelerle pekiştirilmiştir. Verilerin analizi SPSS 22.0 paket programında yapılmıştır. Elde edilen sonuçlar öğrencilerin izolasyon sonucu sosyal kaygı yaşadıklarını tespit etmektedir. Covid-19 pandemi döneminde sosyal izolasyonun 2020-2021 eğitim-öğretim yılı 1. sınıf öğrencilerini etkilediği görülmektedir. Sonuçlar, sosyal kaygı düzeyi ve sosyal değişim arttıkça sosyal, duygusal ve ahlaki gelişimlerinin azaldığını göstermektedir. Anahtar Kelimeler: Covid-19, Pandemi, Sosyal İzolasyon, Kaygı, Sosyal Değişim, Dijital Teknoloji
Pandemi Döneminde Çevrimiçi Eğitimin Çocukların Sosyalleşme Süreçlerine Etkisi: İlkokul Birinci Sınıf Öğrencileri Üzerine İletişim Temelli Bir Araştırma
Keywords: Covid-19; Pandemi; Sosyal İzolasyon; Kaygı; Sosyal Değişim; Dijital Teknoloji; Pandemic; Social Isolation; Anxiety; Social Change; Digital Technology